Systematic study of short- and long-range correlations in RE3TaO7 weberite-type compounds by neutron total scattering and X-ray diffraction. Issue 16 (4th April 2023) - Gussev, Igor M.; O'Quinn, Eric C.; Tucker, Matthew; Ewing, Rodney C.; Overstreet, Cale; Neuefeind, Jörg; Everett, Michelle; Zhang, Qiang; Sprouster, David; Olds, Daniel; Baldinozzi, Gianguido; Lang, Maik
Abstract : The atomic structures of the lanthanide tantalates, Ln3 TaO7, series (Ln = Pr, Tb, Dy, Ho, Tm, Yb) were systematically investigated using total scattering techniques. Abstract : The atomic structures of the lanthanide tantalates, Ln3 TaO7, series (Ln = Pr, Tb, Dy, Ho, Tm, Yb) were systematically investigated using total scattering techniques. High-energy X-ray and neutron diffraction analysis revealed that the long-range structures can be grouped into three distinct families: (1) ordered Cmcm (Ln = Pr), (2) ordered Ccmm (Ln = Tb, Dy, Ho), and (3) disordered, defect-fluorite Fm 3̄ m (Ln = Ho, Tm, Yb). These findings help to clarify the symmetry discrepancy for the already reported long-range structures in the literature. The short-range analysis of neutron total scattering data via pair distribution functions reveals a high degree of structural heterogeneity across length scales for all compounds, with distinct local atomic arrangements that are not fully captured by the average, long-range structure. The short-range structures at the level of coordination polyhedra are better captured by a set of alternative non-centrosymmetric structural models: (1) C 2 cm, (2) C 2221, and (3) C 2 mm . This establishes a short-range multiferroic character for weberite-type tantalates because ferroelectric interactions compete with magnetic correlations. These ferroelectric interactions are particularly pronounced for the disordered compounds Tm3 TaO7 and Yb3 TaO7 . The structural differences among the three families are the result of changes in TaO6 polyhedral tilt (transition between families 1 and 2) and dipolar interactions of off-centered Ta cations (transition between families 2 and 3).